Estudo das percepções de educação ambiental e sustentabilidade dos professores do curso de Agronomia da UFSM: um estudo de caso - Abreu, Lisandra Saldanha de (2007)
As a result of the growing concern about global environmental issues a new society paradigm, the so called sustainable development has emerged as an alternative to the traditional approaches. This study is aimed at identifying professors´ perceptions about environmental education and sustainability, in order to build the related social representations. The design is a qualitative research, basically a study case. The sample was composed of 30 professors of the Agronomy College at the Federal University of Santa Maria (RS,Brazil). Semi-structured interviews were conducted to generate the information; to analyze the information content analysis was employed. A bibliographic review was also performed to build the theoretical framework of the research. The results show that professors´ perceptions in relation to environmental education and sustainability are close to what is called naturalism and anthropocentrism. Professors tend to visualize these topics from the perspective of having a rational use of the natural resources.